Przemiany zachodnioeuropejskiego pogranicza kulturowego pomiędzy Bugiem a Dźwiną i Dnieprem: (polsko-litewsko-białorusko-ukraińskie losy od XV do początku XX wieku) : kurs 14 wykładów - Topolska-Piechowiak, Maria Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In a series of 15 lectures which are aiming for synthesis vital socio-cultural processes from shared and separate histories of Lithuanians, Belarusians, Ukrainians and Poles are introduced (XV-XX century). It is a voice in a debate concerning the state of research of civilization transformations caused by the West and hard-to-depict transformations of ethnic ideas.
Keywords: Tatarzy; Żydzi; Litwa; Ukraina; kościół; społeczeństwo; szkolnictwo; sztuka; architektura; Kresy; religia; Białoruś; 15-20 w.; II (druga) Rzeczpospolita; Karaimi; Ormianie; I (pierwsza) Rzeczypospolita; Wielkie Księstwo Litewskie